1H MRS phantom studies of BNCT 10B‒carrier, BPA–F using STEAM and PRESS MRS sequences: Detection limit and quantification. Issue 2 (2004) - Timonen Timonen, M. M.; Kangasmäki Kangasmäki, A. A.; Savolainen Savolainen, S. S.; Heikkinen Heikkinen, S. S.
Abstract : The quantification of boron neutron capture therapy (BNCT) 10 B‒carrier, L‒p‒boronophenylalanine‒fructose complex (BPA–F) was studied with phantoms using 1 H magnetic resonance spectroscopy sequences PRESS and STEAM at 1.5 and 3.0 T. The results show that typical attainable short echo times of clinical MRS sequences combined with long repetition time result in clinically acceptable quantification accuracy. However, the concentration ratios, which are essential for the treatment planning, can still be reliably measured by using small repetition times. Detection limits of BPA in aqueous phantoms at 1.5 and 3.0 T were evaluated using clinically acceptable measurement time of 10 min, two typical voxel sizes (15 3 and 20 3 mm 3 ) and PRESS and STEAM sequences. The detection limits of BPA in phantom conditions were 0.7 (3.0 T) and 1.4 mM (1.5 T) for PRESS sequence with 20 3 mm 3 voxel.